Boron Fractions in a Vertic Ustochrept as Influenced by Thirteen Years of Fertilization and Manuring - S.P. Datta, K.B. Polara, H.K. Sobhana; Muneshwar Singh, Abir Dey, B.S. Dwivedi, M.C. Meena (Journal of the Indian Society of Soil Science, 2017)
Soil and plant samples were collected after harvest of wheat in 2010 from a long-term experiment on groundnut-wheat sequence that continued since 1996-97 on a Vertic Ustochrept at Junagadh Agricultural University, in order to study the distribution of boron (B) in different fractions and their contribution towards B availability in soil and B uptake by wheat. Treatments included N alone, NP, NPK, 150% of recommended NPK, NPK+farmyard manure (FYM) and an unfertilized control. Five soil B fractions were determined along with hot CaCl2-extractable (available) B. Specifically adsorbed and organically bound B fractions were significantly greater under continuous use of NPK+FYM compared with other treatments, resulting in higher values of available B under NPK+FYM treatment. Soil organic C and cation exchange capacity were the important soil characteristics that governed the distribution of soil B in different fractions. Organically bound B appeared pivotal regarding availability of native B for plant uptake.